6 S.A. ARMOURED DIVISION IN ITALY - Jacobs, F.J.; Bouch, R.J. (Scientia militaria : South African journal of military studies, 2012)
On the victorious conclusion of the campaign in North Africa in May 1943, the Allied Command decided to carry the war into Italy with a view to forcing that country out of the Axis.